Outcomes of percutaneous vertebroplasty in multiple myeloma: a tertiary neurosciences experience with long-term follow-up - Holmes, Hannah E.; Balian, Vartan; Kular, Saminderjit; Batty, Ruth; Connolly, Daniel J. A.; Chantry, Andrew; Martin, Andrew (Frontiers in Oncology, 2024)
Background: Multiple myeloma is diagnosed in 5,800 people in the United Kingdom (UK) each year with up to 64% having vertebral compression fractures at the time of diagnosis. Painful vertebral compression fractures can be of significant detriment to patients’ quality of life. Percutaneous vertebroplasty aims to provide long-term pain relief and stabilise fractured vertebrae. Methods and materials: Data was collected from all cases of percutaneous vertebroplasty performed on patients with multiple myeloma from November 2017 to January 2019. Pain scores were measured using the Visual Analogue Scale (VAS) and Oswestry Disability Index (ODI) pre-procedure, 2 months post procedure and 4 years post-procedure. Procedure related complications and analgesia use were also documented. Results: 22 patients were included with a total of 119 vertebrae treated. Patients reported a significant improvement in overall pain score with a median pre-procedure VAS of 8 and a median post-procedure VAS of 3.5 (p<0.0001). There was a median pre-procedure ODI score of 60% and a median post-procedure ODI score of 36% (p<0000.1). There was improvement across all ODI domains and a 77% reduction in analgesic requirement. There were small cement leaks into paravertebral veins or endplates at 15 levels (12%) which were asymptomatic. There were 8 responders to the long-term follow-up questionnaire at 4 years. This demonstrated an overall stable degree of pain relief in responders with a median VAS of 3.5 and median ODI of 30%. Conclusion: At this centre, vertebroplasty has been shown to reduce both VAS and ODI pain scores and reduce analgesia requirements in patients with VCFs secondary to multiple myeloma with long lasting relief at 4 years post-procedure.